Intrauterine Fetal Goiter: Diagnosis and Management - Ümit Göktolga; K. Emre Karaşahin; Kazim Gezginç; Ulaş Fidan; Ali Ergün; Iskender Başer (Elsevier, 2008)
Summary: Objective: The diagnosis and management of a fetal neck mass encountered during routine antenatal ultrasound screening, and later diagnosed definitely as a intrauterine fetal goiter, is discussed in this case report. Case Report: A 28-year-old primigravida at 36 weeks' gestation with normal vital findings, normal laboratory values, and no history of pathologic findings was examined in our outpatient Department for the first time. Her previous antenatal visits were done in secondary maternal care units. The ultrasound screening revealed polyhydramnios (amniotic fluid index, 21 cm), a homogeneous solid mass of 3.67 × 7.88 cm on the anterior of the fetal neck, and fetal abdominal ascites. Other fetal organs appeared normal. Maternal thyroid panel was in the normal range. The fetus was delivered abdominally at 38 weeks' gestation and diagnosed with defective thyroid hormone biosynthesis. With appropriate treatment, the size of the thyroid gland was observed to decrease. Conclusion: The early diagnosis and appropriate treatment of intrauterine fetal goiter is crucial, owing to the potential mental and motor outcomes of this disease. Key Words: diagnosis, intrauterine fetal goiter, treatment